2018
DOI: 10.1002/cjce.23167
|View full text |Cite
|
Sign up to set email alerts
|

Marble slurry derived hydroxyapatite as heterogeneous catalyst for biodiesel production from soybean oil

Abstract: In this study, utilization of waste marble slurry (MS) as an eco-friendly and low-cost heterogeneous catalyst is introduced for biodiesel production from soybean oil. Catalytic transesterification reaction was done to convert biodiesel from soybean oil using Marble slurry (MS) derived calcined marble slurry (CMS), and hydroxyapatite (HAP) as a heterogeneous catalyst. Marble slurry derived catalysts were characterized by XRD, FTIR, SEM, and TGA with elemental analysis. Hammett indicator method and ion exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 43 publications
(43 reference statements)
2
14
0
Order By: Relevance
“…This is due to the metallic Pt around the HAp core as well as the microporous nature of HAp/Pt, which suppresses the yield. This finding is similar to that of Gupta et al [ 18 ] who reported a higher (94%) yield for MS‐based HAp than with any other type of catalyst used in their work. In the present work, initially the HAp/Pt was calcinated at 973 K (700°C) for 2 hours and then the catalytic reaction was initiated; however, the conversion to biodiesel was significantly low.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This is due to the metallic Pt around the HAp core as well as the microporous nature of HAp/Pt, which suppresses the yield. This finding is similar to that of Gupta et al [ 18 ] who reported a higher (94%) yield for MS‐based HAp than with any other type of catalyst used in their work. In the present work, initially the HAp/Pt was calcinated at 973 K (700°C) for 2 hours and then the catalytic reaction was initiated; however, the conversion to biodiesel was significantly low.…”
Section: Resultssupporting
confidence: 91%
“…The observed results show that the developed pure HAp corn-like nanoparticles and HAp/Pt core shell NRs could be used as environmentally benign nanobiocatalysts for clean green energy production. However, the changing reaction parameters and mass production Marble slurry Soybean oil 6 1:9 3 90.0 Gupta et al [18] Marble slurry-based HAp Soybean oil 6 1:9 3 94.0 Gupta et al [18] Chicken bone derived HAp Waste cooking oil 5 g 1:15 4 89. 3 Farooq et al [39] Waste animal bone-based HAp Tylosema esculentum kernel oil 20 1:18 4 96.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-temperature calcination will give the sintering effect on HAP which could lead to agglomeration of catalyst particles [11]. Gupta et al [23] also explained that the sintering phenomena could result in particles to be more circular shaped and has a smoother surface.…”
Section: Catalyst Surface Morphology Analysismentioning
confidence: 99%
“…The theme of CHEMCON 2016 was “Chemical Engineering: Towards Sustainable Development.” CHEMCON2016 was organized by IIChE Chennai Regional Centre in association with AC College of Technology, Anna University, Indian Institute of Technology Madras, and Central Leather Research Institute Adyar Chennai. As part of CHEMCON2016, the international symposiums “Indo‐Canada International symposium on Sustainable Energy—Energy for all” and Indo‐US International symposium on “Membrane Technology” were held …”
mentioning
confidence: 99%